Clinical And Radiographical Evaluation Of Silver Nanoparticles Formulations On Pulpectomized Primary Molar - Reda Mustafa Abu Elrish, Ahmed; Farouk Barakat, Ibrahim; Nabil Abbas, Alaa (Journal of Neonatal Surgery, 2025)
Objectives: This study was directed to evaluate clinical and radiographical effect of silver nanoparticles formulations on pulpectomized primary molar. Subjects and methods: Seventy two Children between the ages of 4 and 8 who had multiple- rooted primary posterior teeth that needed pulpectomy therapy were chosen. The Nano-Gate helped with the root canal irrigant solutions and oturating materials. Results: The findings of this RCT revealed that AgNPs have higher Clinical And Radiographic results than NaOCl, this could be attributed to the fact that AgNPs inhibits the development of biofilms and decreases bacterial adhesion. The clinical and radiographic follow-up results of this RCT revealed that the use of AgNPs gel as intracanal medication had better success rates than the use of Ca(OH)2 medication. Furthermore, the results of this RCT revealed that the use of AgNPs formulations had better success rates with passive ultrasonic irrigation (PUI) system and negative pressure irrigation system (EndoVac) than conventional syring system. Conclusion: Based on the results of this study, PUI and the EndoVac negative pressure system are superior to conventional endodontic needles in terms of their ability to eradicate the E. Faecalis, AgNPs solution was able to reduce colonies of E. faecalis, indicating its potential use as a root canal irrigation, AgNPs gel had higher clinical success rate than Ca(OH)2, indicating its potential use as a interappointment medicament.